Spontaneous poisoning by Ateleia glazioviana (leg. Papilionoideae) in sheep and goats in the West region of Santa Catarina - Gava,Aldo (2021)
ABSTRACT: This study reported the epidemiological data and the clinical and pathological conditions of spontaneous poisoning by Ateleia glazioviana in sheep and goats in the West region of Santa Catarina. The small ruminants were located in a place where there was a large amount of young plants of A. glazioviana and showing signs of consumption. The stock of sheep was composed of 250 animals, of which 45 died. In the goat herd, there were 28 animals, and of these, 27 died, and one was sacrificed. The main clinical signs were weight loss, fatigue, slow-walk, and eventually submandibular and facial edema. Some animals were found dead, and others died suddenly after being moved. Abortions and the birth of weak lambs were also observed. In total, five sheep and one goat were necropsied. The main macroscopic lesions were associated to eccentric cardiac hypertrophy and moderate, multifocal white areas in the epicardium and myocardium. Two sheep showed marked edema in the subcutaneous tissue of the head and neck and it could be noted hydrothorax and hydroperitoneum and liver with a nutmeg-like appearance. Histological changes were relevant in the myocardium. They consisted of fibrosis and myofiber necrosis associated with macrophage infiltrate, multifocal, low and marked swelling of cardiomyocytes with loss of fibrillarystriae, and increased nuclear volume. In two sheep, there was still congenital hepatic, as well as marked centrilobular and diffuse areas.